2017
DOI: 10.1128/aem.00585-17
|View full text |Cite
|
Sign up to set email alerts
|

Surface Sensing for Paenibacillus sp. NAIST15-1 Flagellar Gene Expression on Solid Medium

Abstract: A rhizosphere Gram-positive bacterial isolate, Paenibacillus sp. NAIST15-1, exhibits intriguing motility behavior on hard agar medium. Paenibacillus sp. shows increased transcription of flagellar genes and hyperflagellation when transferred from liquid to solid medium. Hyperflagellated cells form wandering colonies that are capable of moving around on the surface of medium containing Ն1.5% agar. Transposon mutagenesis was used to identify genes critical for motility. In addition to flagellar genes, this mutage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…We identified the Type I secretion system that secretes RTX-like adhesion required for auto-aggregation and biofilm formation. The gene like LapB (Type I secretion system ATPase), LapC (membrane fusion protein), LapE (outer membrane component), LapD (membrane bound c-di-GMP receptor), LapP (transglutaminase like cystine protenease), LapL (peptidoglycan associated lipoproteins), and RTX (T1SS-secreted agglutinins) were identified [ 85 ]. The presence of flagella, flagellar-associated protein and flagellar regulatory protein helps the bacteria for their colonization and stress survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified the Type I secretion system that secretes RTX-like adhesion required for auto-aggregation and biofilm formation. The gene like LapB (Type I secretion system ATPase), LapC (membrane fusion protein), LapE (outer membrane component), LapD (membrane bound c-di-GMP receptor), LapP (transglutaminase like cystine protenease), LapL (peptidoglycan associated lipoproteins), and RTX (T1SS-secreted agglutinins) were identified [ 85 ]. The presence of flagella, flagellar-associated protein and flagellar regulatory protein helps the bacteria for their colonization and stress survival.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study demonstrated the presence of flagellum in Paenibacillus sp. NAIST15-1, which showed the increased transcription of flagellar genes and hyper-flagellation when transferred from liquid to solid medium [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that restricting the flagellar rotation by viscous medium results in induction of flagellar gene transcription and activation of the DegSU two-component system in Paenibacillus sp. NAIST15-1 (Kobayashi et al, 2017). Accordingly, we tested whether an increased viscosity of the 8 medium changes the transformability in B. subtilis.…”
Section: Increased Viscosity Enhances Competence In B Subtilismentioning
confidence: 99%